A new 3D indoor/outdoor spatial model for indoor emergency response facilitation. (July 2015) - Tashakkori, Hosna; Rajabifard, Abbas; Kalantari, Mohsen
Abstract: Increasing size and complexity of indoor structures and increased urbanization has led to much more complication in urban disaster management. Contrary to outdoor environments, first responders and planners have limited information regarding the indoor areas in terms of architectural and semantic information as well as how they interact with their surroundings in case of indoor disasters. Availability of such information could help decision makers interact with building information and thus make more efficient planning prior to entering the disaster site. In addition as the indoor travel times required to reach specific areas in the building could be much longer compared to outdoor, visualizing the exact location of building rooms and utilities in 3D helps in visually communicating the indoor spatial information which could eventually result in decreased routing uncertainty inside the structures and help in more informed navigation strategies. This work aims at overcoming the insufficiencies of existing indoor modelling approaches by proposing a new Indoor Emergency Spatial Model (IESM) based on IFC. The model integrates 3D indoor architectural and semantic information required by first responders during indoor disasters with outdoor geographical information to improve situational awareness about both interiors of buildings as well as their interactions with outdoor components. The model is implemented and tested using the Esri GIS platform. The paper discusses the effectiveness of the model in both decision making and navigation by demonstrating the model's indoor spatial analysis capabilities and how it improves destination travel times. Highlights: A 3D Indoor Emergency Spatial Model (IESM) is developed. IESM integrates geometric and semantic mission critical indoor/outdoor information. The model is implemented for a test area using GIS technologies. IESM improves 3D visualization and situational awareness of the emergency site. IESM optimizes indoor navigation strategies and reaching times.